Withaferin A inhibits lysosomal activity to block autophagic flux and induces apoptosis via energetic impairment in breast cancer cells. (29th January 2019) - Muniraj, Nethaji; Siddharth, Sumit; Nagalingam, Arumugam; Walker, Alyssa; Woo, Juhyung; Győrffy, Balázs; Gabrielson, Ed; Saxena, Neeraj K; Sharma, Dipali
Abstract: Withaferin A (WFA), a steroidal lactone, negatively regulates breast cancer growth however, its mechanisms of action remain largely elusive. We found that WFA blocks autophagy flux and lysosomal proteolytic activity in breast cancer cells. WFA increases accumulation of autophagosomes, LC3B-II conversion, expression of autophagy-related proteins and autophagosome/lysosome fusion. Autolysosomes display the characteristics of acidic compartments in WFA-treated cells; however, the protein degradation activity of lysosomes is inhibited. Blockade of autophagic flux reduces the recycling of cellular fuels leading to insufficient substrates for tricarboxylic acid (TCA) cycle and impaired oxidative phosphorylation. WFA decreases expression and phosphorylation of lactate dehydrogenase, the key enzyme that catalyzes pyruvate-to-lactate conversion, reduces adenosine triphosphate levels and increases AMP-activated protein kinase (AMPK) activation. AMPK inhibition abrogates while AMPK activation potentiates WFA's effect. WFA and 2-deoxy-d-glucose combination elicits synergistic inhibition of breast cancer cells. Genetic knockout of BECN1 and ATG7 fails to rescue cells from WFA treatment; in contrast, addition of methyl pyruvate to supplement TCA cycle protects WFA-treated cells. Together, these results implicate that WFA is a potent lysosomal inhibitor; energetic impairment is required for WFA-induced apoptosis and growth inhibition and combining WFA and 2-DG is a promising therapeutic strategy for breast cancer. Abstract : Study shows that WFA mediated blockade of autophagic flux involves inhibition of lysosomal proteolytic activity reducing the recycling of cellular fuels. WFA induces apoptosis and inhibits growth via energetic impairment and WFA and 2-deoxyglucose combination elicits synergistic inhibition.